Efeitos da terapia celular, com células tronco mesenquimais do tecido adiposo, e do infiltrado de plasma rico em plaquetas no tratamento da osteoartrite não responsiva ao tratamento medicamentoso - Schweich, Laynna de Carvalho (2021)
The increase in individuals with Osteoarthritis (OA) has generated an increase in public spending on monitoring and maintaining treatments, which have lasted for years and are still not resolvable. This study is the first cell therapy proposal for OA carried out in the Brazilian Public Health System, in the State of Mato Grosso do Sul. The objective of the work was divided into two stages: the laboratory which aimed to analyze the quality of adipose-derived stem cells (ADSCs ) cultured from the 1st to the 10th passage, and later the clinic, which in an unprecedented way analyzed and compared 4 types of interventions in patients with OA: platelet-rich plasma (PRP), ADSCs, ADSCs + PRP and the standard surgical procedure performed in our hospital. The analysis of the ADSCs passages was performed by immunophenotyping assay, cell differentiation, comet assay, cytological and molecular cell death assay, morphological analysis, apoptosis, membrane integrity and viability in the flow cytometer. The evaluation of the patients was carried out by applying the questionnaires of WOMAC, SF-36 and EVA, and by analyzing the synovial fluid (inflammatory cytokines, enzymatic, colorimetric and viscosity analysis). Regarding the quality of ADSCs, the trypsinization process carried out during cultivation did not interfere with the genomic stability of the cells. But as of the 6th pass, ADSCs started to modify its capacity for juxtaposed deposition and proliferation in monolayer, as well as increasing its size. Cell viability was significantly reduced only on the 10th passage, and it was proven that this was due to apoptosis due to changes in membrane permeability. The results of the questionnaires applied to the patients, showed a greater improvement in the scores of the analyzed domains (initial x final evaluation / by group and final values / between groups) in the ADSCs + PRP group, followed by the ADSCs and PRP group. In the evaluation of inflammatory cytokines, there was a significant reduction (initial x final / per group) of the IL-1b cytokine only in the ADSCs + PRP (40%) and ADSCs (31%) groups, of IL-6 in the ADSCs + PRP group ( 72%), IL-8 in the ADSCs + PRP (50%) and ADSCs (31%) groups, and TNF in the ADSCs + PRP group (46%). Only the reductions in the ADSCs + PRP group were considered significant in the analysis of the final values / between the groups. There was also a significant increase in the amount of total proteins (79%) in the control group and polymorphonuclear cells (47%) in the ADSCs + PRP group. In view of the results, we observed that therapies with ADSCs + PRP and only ADSCs are safe and effective for improving pain, functional capacity and joint inflammation in patients with OA. However, the use of ADSCs + PRP is considered the most promising treatment option in helping to manage this pathology.